On the detection of surface spin freezing in iron oxide nanoparticles and its long-term evolution under ambient oxidation. (18th November 2020) - Ghoshani, M; Sánchez, E H; Lee, S S; Singh, G; Yaacoub, N; Peddis, D; Mozaffari, M; Binns, C; De Toro, J A; Normile, P S
Abstract: Exchange bias (EB) effects linked to surface spin freezing (SSF) are commonly found in iron oxide nanoparticles, while signatures of SSF in low-field temperature-dependent magnetization curves have been much less frequently reported. Here, we present magnetic properties of dense assemblies of similar-sized (∼8 nm diameter) particles synthesized by a magnetite (sample S1) and a maghemite (sample S2) method, and the influence of long-term (4 year) sample aging under ambient conditions on these properties. The size of the EB field of the different sample (fresh or aged) states is found to correlate with (a) whether a low-temperature hump feature signaling the SSF transition is detected in out-of-phase ac susceptibility or zero-field-cooled (ZFC) dc magnetization recorded at low field and with (b) the prominence of irreversibility between FC and ZFC curves recorded at high field. Sample S1 displays a lower magnetization than S2, and it is in S1 where the largest SSF effects are found. These effects are significantly weakened by aging but remain larger than the SSF effects in S2, where the influence of aging is considerably smaller. A non-saturating component due to spin disorder in S1 also weakens with aging, accompanied by, we infer, an increase in the superspin and the radius of the ordered nanoparticle cores. X-ray diffraction and Mössbauer spectroscopy provide indication of maghemite-like stoichiometry in both aged samples as well as thicker disordered particle shells in aged-S1 relative to aged-S2 (crystallographically-disordered and spin-disordered according to diffraction and Mössbauer, respectively). The pronounced diminution in SSF effects with aging in S1 is attributed to a (long-term) transition, caused by ambient oxidation, from magnetite-like to maghemite-like stoichiometry, and a concomitant softening of the spin-disordered shell anisotropy. We assess the impact of this anisotropy on the nature of the blocking of the nanoparticle superspins.